Pengaruh Model Brain Based Learning Terhadap Hasil Belajar Ipa Pada Siswa Kelas V SD Negeri 2 Cengal - nefi afila; Destiniar; Adrianus Dedy (CV. ITTC INDONESIA, 2023)
learning outcomes in fifth grade students of SD negeri 2 Cengal. This research is a quantitative study using experimental methods with the type of Quasi Experimental Design. The variables of this study consisted of independent variables, namely the brain-based learning model (X) and the dependent variable, namely science learning outcomes (Y). The study population was all V.A and V.B class students totaling 61 students and the sample size was 61 students. Data collection techniques using tests. Instruments to measure science learning outcomes using pretest and posttest in the form of multiple choice questions. The experimental class group obtained an average pretest score of 72.5, and a posttest of 82.33 and the control class obtained an average pretest score of 73.22 and a posttest of 72.74. The results of the t test with Sig 0.000 0.05 and the results of t count 3.784 t table 2.001, it can be concluded that there is a significant effect of the brain-based learning model on science learning outcomes in fifth grade students of SD negeri 2 Cengal. Keywords: brain based learning model, and science learning outcomes